2020
DOI: 10.1002/bit.27280
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis detection via automated algorithms to analyze biomarker translocation in reporter cells

Abstract: Rapid, efficient, and robust quantitative analyses of dynamic apoptotic events are essential in a high‐throughput screening workflow. Currently used methods have several bottlenecks, specifically, limitations in available fluorophores for downstream assays and misinterpretation of statistical image data analysis. In this study, we developed cytochrome‐C (Cyt‐C) and caspase‐3/‐8 reporter cell lines using lung (PC9) and breast (T47D) cancer cells, and characterized them from the response to apoptotic stimuli. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…Although measurement of higher concentrations of Ca 2+ is one of the limitations of the proposed technique, the error arising from unwanted pixels was minimized using background correction, as mentioned in Supplementary Figure S1. Although the expression of single reporter biomolecules can be used for live monitoring and for generating dynamic data on apoptotic processes using high-resolution microscopy, 40 the major disadvantage is lower transfection efficiency. This method has the ability to monitor transfected cells, which are around 30-40% of the whole cell population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although measurement of higher concentrations of Ca 2+ is one of the limitations of the proposed technique, the error arising from unwanted pixels was minimized using background correction, as mentioned in Supplementary Figure S1. Although the expression of single reporter biomolecules can be used for live monitoring and for generating dynamic data on apoptotic processes using high-resolution microscopy, 40 the major disadvantage is lower transfection efficiency. This method has the ability to monitor transfected cells, which are around 30-40% of the whole cell population.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorometric characteristics have to be chosen such that there are no overlapping signals. 33,40 It was observed that imaging with multiple dyes, including PI-Fluo-4 and Hoechst-Fluo-4, leads to overlapping signals, different rates of internalization of the dye, and modification in toxicity levels. Hence, to quantify the toxicity or lytic process in the presence of norepinephrine, it was not possible to perform imaging using combinations of Fluo-4 and PI or Fluo-4 and Hoechst.…”
Section: Discussionmentioning
confidence: 99%
“…Although the expression of single reporter biomolecules can be used for live monitoring and for generating dynamic data on apoptotic processes using high-resolution microscopy, 40 the major disadvantage is lower transfection efficiency. This method has the ability to monitor transfected cells, which are around 30–40% of the whole cell population.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorometric characteristics have to be chosen such that there are no overlapping signals. 33,40 It was observed that imaging with multiple dyes, including PI–Fluo-4 and Hoechst–Fluo-4, leads to overlapping signals, different rates of internalization of the dye, and modification in toxicity levels. Hence, to quantify the toxicity or lytic process in the presence of norepinephrine, it was not possible to perform imaging using combinations of Fluo-4 and PI or Fluo-4 and Hoechst.…”
Section: Discussionmentioning
confidence: 99%